Meningkatkan Hasil Belajar Sejarah Kebudayaan Islam Menggunakan Metode Inside Outside Circle - Fadhilah Fadhilah; Rusdin Rusdin (Al-Fikr: Jurnal Pendidikan Islam, 2018)
This research is motivated by the problem of low student learning outcomes in the subjects of Islamic Cultural History and does not meet the competency standards according to curriculum demands. This is due to the lack of student learning motivation, and lack of teacher variation in using learning methods. Therefore the researcher chose one of the learning methods namely the Inside-Outside Circle method to improve student learning outcomes. The Inside-Outside Circle method is a learning method by making small circles and large circles, where seven people make an inner circle facing outward and seven people make an outer circle facing inward. The purpose of the research is to improve the quality of learning, especially in the subjects of Islamic Cultural History (SKI). The subjects of this study were students of class XI IPA 2 MAN Model Sorong City in the even semester of the academic year 2017/2018 totaling 29 people. This research was conducted in 2 cycles, namely, cycle 1 carried out 2 meetings and cycle II 2 meetings. The object of this study is student learning outcomes which are divided into 3 domains, namely cognitive, affective and psychomotor. Data collection techniques are done using observation sheets and test sheets during the action and documentation of learning activities. The collected data were analyzed both qualitative and quantitative data. Qualitative data were analyzed by data exposure stages. While quantitative data using descriptive statistical analysis with statistical data processing software SPSS 23.0 and Microsoft Excel 2010. From the results of this study, it can be concluded that an increase in learning outcomes of Islamic Cultural History in class XI MIPA 2 MAN Sorong City Model after applying the Inside-Outside Circle method